Thermodynamic Properties of Molecular Crystals Calculated within the Quasi-Harmonic Approximation - Červinka, Ctirad; Fulem, Michal; Stoffel, Ralf Peter; Dronskowski, Richard (The journal of physical chemistry. A, 2016)
A computational study of the possibilities of contemporary theoretical chemistry as regards calculated thermodynamic properties for molecular crystals from first-principles is presented. The study is performed for a testing set of 22 low-temperature crystalline phases whose properties such as densities of phonon states, isobaric heat capacities, and densities are computed as functions of temperature within the quasi-harmonic approximation. Electronic structure and lattice dynamics are treated by plane-wave based calculations with optPBE-vdW functional. Comparison of calculated results with reliable critically assessed experimental data is especially emphasized.